Spectrophotometric Determination of Candesartan Cilexetil in Presence of Its Alkaline Induced Degradation Product - A. Al-Arfaj, Nawal; A. Al-Onazi, Wedad; M. El-Brashy, Amina (Asian Journal of Chemistry, 2010)
The present work describes a simple stability-indicating second derivative spectrophotometric assay method for determination of an antihypertensive drug, candesartan cilexetil in presence of its alkaline degradation product, candesartan. The method was satisfactory validated with respect to linearity, precision, accuracy, selectivity and sensitivity. The response was linear in the concentration range of 4-32 μg mL-1 (r = 0.99995) at wavelength 291.2 nm, which was the zero crossing point of candesartan in methanol. The detection and quantitation limits were 0.33 and 1.00 μg mL-1, respectively. The suggested method was successfully applied for the analysis of candesartan cilexetil in bulk and in commercial tablets. The results were favourably compared statistically to that obtained by a reference method.